28.1k views
3 votes
If f(x)=6x^3-4 and g(x)=2x+2 find (f-g) (x)

a.6x^2-2x-2
b.6x^3-2x-6
c.2x-5x^3
4x^3-6

2 Answers

4 votes
(f-g)(x)=f(x)-g(x)=
(6x³-4)-(2x+2)=
6x³-4-2x-2=
6x³-2x-4-2=
6x³-2x-6

B is answer
User Spuder
by
5.8k points
6 votes

Answer:

B is correct

Explanation:

We are given two function f(x) and g(x). We need to calculate (f-g)(x)


f(x)=6x^3-4


g(x)=2x+2


(f-g)(x)=f(x)-g(x)


(f-g)(x)=(6x^3-4)-(2x+2)

Using Distributive property (-2x-2)


(f-g)(x)=6x^3-4-2x-2

Combine like terms (-4-2=-6)


(f-g)(x)=6x^3-2x-6

Thus, (f-g)(x)=6x³-2x-6.

User Lbenedetto
by
6.1k points